When terroir lost the plot. On re-grounding wine - Pavoni, A. (Studi Culturali, 2025)
Terroir lost the plot when its speculative, relational potential has been frozen into a "dispositif" that reduces soil to inert substrate, land to a legally coded space of exception, and place to a socio-cultural fetish tied to identity, hierarchy and nationalist localism. In the context of planetary urban-rural transformations and soil crisis, this paper reframes terroir as an emergent "agencement" of soil, land and place, whose multispecies aliveness exceeds both protectionist appellation regimes and the «democratic», market-led critique that claims to liberate wine from tradition. Focusing on Natural Wine as a heterogeneous but movement-like field, the paper argues that its minimal-intervention ethos articulates an "anarchic critique" of terroir through three operations: reanimating soils, unarchiving land and trans-localising place. Natural Wine protocols, practices and participatory forms of verification thus decouple terroir from static origin, repositioning it as a grounded, more-than-human normativity and a site for alternative political-ecological value.